Aloe and honey : tales from town and country - Mxakwe, Mzamadoda Theophilus (Department of English Language and Literature, 2014)
The Black South African literary oeuvre has as its dominant background township life. There has been a considerable neglect of village or rural setting. Even the proliferation of writing that has been regarded as depicting genuine African experience has fallen short of remedying this malady. There is a paucity of writings that endeavour to depict rural communities, and even where South African writers attempted to depict rural community, theirs has been an indolent attempt, as evinced by a lack of insight in such writings. One example is Matshoba's Call Me Not A Man. which is merely a glimpse into the rural setting. This shortcoming, coupled with a travesty of the rural setting, suggests a non-existence of the rural community. Whether South African writers, especially, Black writers, eschew rural setting deliberately or not is open to debate. Hence my project has as its paramount aim an endeavour to expose authentic rural realities. This collection, therefore, portrays rural life against the backdrop of city life. This paradoxical juxtapositioning is a deliberate attempt to enable the reader to extricate real-life happenings from both scenarios, and have a sound judgement about his/her observation.